The Influence of Employee Engagement and Work Environment on Employee Performance at PT. Agronusa Alam Perkasa - Thalia, RA Dinda; Aliya, Sabeli; Gunarto, Muji; Helmi, Sulaiman (Jurnal Ekonomi, 2024)
This study aims to investigate the influence of Employee Engagement and Work Environment on Employee Performance at PT Agronusa Alam Perkasa, an oil palm plantation company. Data was obtained through surveys and interviews with company employees. The data analysis technique used was multiple linear regression. The results showed that Employee Engagement has a positive, although not statistically significant, influence on Employee Performance. In contrast, Work Environment has a significant positive influence on Employee Performance. This indicates that aspects of a conducive work environment, such as good lighting and noise, play an important role in improving employee performance. Therefore, companies need to pay greater attention to improving the Work Environment as a strategy to improve employee performance. The limitation of this study is that it does not consider other factors that may affect employee performance. Future research should include these additional factors to gain a more comprehensive understanding of the factors.